An ethno-botanical study of medicinal plants in Dilla Zuria Woreda of Gedo Zone, Southern Ethiopia - Tadeyos Mesfin; Wendawek Abebe (Global Journal of Ecology - Peertechz Publications, 2022)
The present study was carried out to investigate the diversity and use of medicinal plants, and to document the indigenous knowledge of the local community. The typical ethnobotanical methodologies were applied during the study. Eighty-one informants were selected by the preferential sampling of which 61 were males and 20 were females. The selected individuals were considered knowledgeable in their view of medicinal plants. Data were collected using semi-structured interviews, field observation, group discussion, and specimen collection. Informant consensus, preference ranking, direct matrix ranking, and informant consensus factor were computed. A total of 105 plant species were identified belonging to 105 genera and 52 families. Of the total plants, 70 plant species have medicinal values and are recorded from the study area. Based on the study, the family Asteraceae was found to be the most prominent family with 8 species under 8 genera followed by Fabaceae which comprise 6 species under 6 genera. Of medicinal plants collected in the area, 79.66% were used to treat human ailments, 17.79% were used to treat both human and livestock ailments, and 2.54 % were used to treat livestock ailments. Of the total medicinal plants, herbs were the dominant making 45 (47.5%) followed by shrubs 35(29.46%), trees 15(15.75%), and climbers 10(7.35%). Leaf (41%) was the most frequently utilized medicinal plant part followed by root which is (18%). About 44 different kinds of diseases in the local community were identified and have been treated by existing and identified medicinal plants. The most widely used method of preparation was in the form of crushing (44%) followed by boiling (17%) and powdering (10%). The majority of preparations used fresh parts (53.63%) more than the dried forms (36.81%). Oral (50%) and dermal (30.92%) applications were the common routes of administration. Agricultural expansion, overgrazing, over-harvesting of plants for different household utensils, and other human-induced problems were the major threats to natural habitats in general and medicinal plants in particular. Therefore, it is recommended that awareness creation through training and education with the participation of government and non-governmental organizations on sustainable use and conservation of plant resources should be encouraged.